A method for preparing green high-performance slag micropowder

By combining physical excitation and chemical excitation methods, green high-performance slag powder was prepared, which solved the problem of low activity of slag powder, significantly improved the strength and performance of concrete, and realized an environmentally friendly and energy-saving preparation process.

CN118771766BActive Publication Date: 2025-02-11JIANGSU RUNTIAN BUILDING MATERIALS (GRP) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410858050.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2025-02-11
Estimated Expiration
2044-06-28

AI Technical Summary

Technical Problem

The existing slag micropowder has low activity, resulting in insufficient concrete strength and performance, and the chemical excitation method has environmental pollution problems.

Method used

By rolling and ball milling the slag, glass, lithium slag and alkali slag, and powdering it through wetting, soaking, freezing and vacuum drying cycles, combined with the addition of zinc nitrate and 2-methylimidazole to the alcohol solvent for reaction, the preparation is made Green high-performance slag powder is produced.

Benefits of technology

The hydration gelling activity of slag micro powder is significantly improved, the specific surface area and surface energy are increased, the strength and performance of concrete are improved, and the method is environmentally friendly, energy-saving, and there is no waste generation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004918565100000051
    Figure BDA0004918565100000051
  • Figure BDA0004918565100000061
    Figure BDA0004918565100000061
Patent Text Reader

Abstract

The invention discloses a preparation method of green high-performance slag micropowder, which belongs to the technical field of comprehensive utilization of solid wastes. The method comprises the following steps: pulverizing slag, glass, lithium slag and alkali slag respectively to obtain fine powder; weighing the fine powders of each raw material according to a ratio and mixing and sand-grinding; the mixed micropowder is sequentially subjected to wetting and soaking, freezing and vacuum drying, and the wetting and soaking, freezing and vacuum drying processes are repeated, and then the mixed micropowder is dispersed in an alcohol solvent, zinc nitrate and 2-methylimidazole are added, the mixed system is stirred at room temperature for reaction for 0.5-6h, and after solid-liquid separation, the mixed system is sequentially washed and dried to obtain the green high-performance slag micropowder; the invention improves the hydration and gelling activity of the slag micropowder by combining a physical excitation method with a chemical excitation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of comprehensive utilization of solid waste, and in particular to a method for preparing green high-performance slag micropowder. Background Art

[0002] Slag is a byproduct of the blast furnace ironmaking process. During the ironmaking process, iron oxide is reduced to metallic iron at high temperatures, and impurities such as silicon dioxide and aluminum oxide in iron ore react with lime to form a molten material with silicate and aluminosilicate as the main components. After air or water quenching, it becomes a loose, porous granular material, which is granulated blast furnace slag, or slag for short. The chemical composition of slag includes oxides such as CaO, SiO2, Al2O3, MgO, MnO, Fe2O3, and a small amount of sulfides such as CaS and MnS. Generally speaking, the content of CaO, SiO2 and Al2O3 accounts for more than 90%. The chemical composition of slag is basically the same as that of cement, except that the CaO content is lower and the SiO2 content is higher. In addition, alkaline slag with a higher CaO content also contains components such as dicalcium silicate, so the slag itself has weak hydraulic properties; therefore, slag powder can be used as a raw material for concrete to replace more expensive cement, and can also be used as a modifier to improve the performance of concrete. At present, slag powder is mainly used in the production of cement mixing materials and concrete admixtures.

[0003] The activity of slag powder plays a decisive role in improving the strength and performance of concrete. There are many ways to improve the activity of slag powder. One is physical stimulation, which relies on grinding process, grinding equipment and grinding technology to improve the activity of slag powder, that is, to achieve a relatively high specific surface area of ​​slag powder, better particle morphology, and a larger particle grading distribution range; according to relevant data reports, the specific surface area of ​​slag powder is only 480m 2 / kg or more, and most of the particles are distributed between 2-40μm, its activity can be fully exerted. At present, mechanical methods are mainly used to prepare high-activity slag powder. Due to equipment limitations, granulated blast furnace slag has a high hardness and is difficult to grind. The specific surface area of ​​slag powder obtained by conventional horizontal ball mills is generally 350-370m 2 / kg, the three-day activity index is generally lower than 65%, the early strength is obviously low, the potential activity cannot be fully exerted, and the performance is also greatly limited; the second is to improve the activity of slag powder by chemical excitation method, that is, to adjust the surface chemical composition of slag powder by chemical excitation method, thereby improving the activity of slag powder, but chemical methods generally have serious environmental pollution problems. Summary of the invention

[0004] In view of the above problems, the present invention provides a method for preparing green high-performance slag powder.

[0005] The purpose of the present invention is achieved by the following technical solutions:

[0006] A method for preparing green high-performance slag micropowder comprises the following steps:

[0007] (1) Rolling and ball milling slag, glass, lithium slag and alkali slag to obtain fine powder of each raw material;

[0008] (2) weighing and mixing the fine powders of the raw materials according to the ratio, and preparing the first mixed fine powder after sand grinding;

[0009] (3) soaking the first mixed micropowder for 1-24 hours, freezing after solid-liquid separation, and then vacuum drying, repeating the soaking, freezing and vacuum drying process to obtain a second mixed micropowder;

[0010] (4) dispersing the second mixed micropowder in an alcohol solvent, adding zinc nitrate and 2-methylimidazole, stirring the mixed system at room temperature for reaction for 0.5-6 hours, and washing and drying in sequence after solid-liquid separation to obtain the green high-performance slag micropowder.

[0011] In some preferred embodiments, in step (1), the particle size of the fine powder of the slag and the lithium slag is 200-300 mesh; the particle size of the fine powder of the glass and the alkali slag is 200-400 mesh.

[0012] In some preferred embodiments, in step (2), the mass fraction ratio of the fine powders of the slag, the glass, the lithium slag and the alkali slag is 100:(4-8):(2-6):(1-5).

[0013] In some preferred embodiments, the grinding balls used in the sand mill in step (2) are made of yttria-stabilized zirconia ceramic material, and the diameters thereof include two or three of 3 mm, 1 mm, and 0.5 mm, and the mass ratio of the grinding balls with diameters of 3 mm, 1 mm, and 0.5 mm is (0-2):(0.5-3):1; the ratio of the mass of the grinding balls to the total mass of the material is (3-8):1; the main machine speed of the sand mill is 500-1600 rpm, and the sand milling time is 1-10 h.

[0014] In some preferred embodiments, the specific surface area of ​​the first mixed micropowder is 350-400m 2 / kg, D95 is not greater than 40μm.

[0015] In some preferred embodiments, the freezing temperature in step (3) is -4°C to -20°C; the vacuum drying temperature is 25-60°C, and the drying time is 1-8h.

[0016] In some preferred embodiments, the total number of repetitions of the wetting, soaking, freezing and vacuum drying processes in step (3) is 2-4 times.

[0017] In some preferred embodiments, in step (4), the alcohol solvent is one or more of methanol, ethanol, isopropanol, n-butanol, 2,2-dimethylpropanol, n-hexanol, n-heptanol, and n-octanol.

[0018] In some preferred embodiments, the concentration of zinc nitrate in the mixed system is 0.005-0.01 mol / L, and the concentration of 2-methylimidazole in the mixed system is 0.01-0.02 mol / L.

[0019] Another aspect of the present invention is to provide a green high-performance slag powder, which is prepared by the above-mentioned preparation method.

[0020] The beneficial effects of the present invention are:

[0021] (1) In view of the problem that the existing slag powder has low activity, the present invention provides a method for preparing green high-performance slag powder, which improves the hydration and gelation activity of the slag powder by combining a physical excitation method with a chemical excitation method. Specifically, the present invention adds glass powder and alkali slag to the slag, and performs a synchronous dry-wet-freeze-thaw treatment on the mixed powder through a wetting-immersion-freeze-drying cycle, so that the internal crystal structure thereof becomes irregular and undergoes a multi-phase crystal transformation, resulting in lattice defects, an increase in specific surface area, an increase in surface energy, etc., so that the thermodynamic properties, crystallographic properties, The physical and chemical properties change, thereby improving the activity of the slag powder; at the same time, the present invention also in situ coats the surface of the slag powder with a layer of zeolite imidazole framework material-8, and utilizes the zeolite imidazole framework material-8 on the surface to concentrate a large number of carbon dioxide molecules on the surface of the slag powder to promote its hydration. Furthermore, the solubility of the alkali slag in water is increased due to the presence of carbon dioxide, thereby improving the alkalinity of the slag powder in the hydration system. Furthermore, the glass powder is converted into silicate under enhanced alkaline conditions to further promote gelation; the present invention also improves the performance of the blended concrete by adding lithium slag.

[0022] (2) The preparation method of the slag micropowder of the present invention is relatively simple and does not involve complicated chemical modification and doping. The in-situ coating of the zeolite imidazole framework material-8 is carried out in an alcohol solvent. The reaction solvent, reactants and washing solvent can be directly reused. No waste is generated in the process. The preparation method is environmentally friendly and energy-saving. DETAILED DESCRIPTION

[0023] The present invention is further described in conjunction with the following examples.

[0024] Example 1

[0025] A green high-performance slag micropowder, the preparation method of which comprises the following steps:

[0026] (1) Slag, glass, lithium slag and alkali slag are respectively subjected to roller pressing and ball milling to obtain fine powder of each raw material; the roller pressing pressure is 100-120 MPa; the grinding balls of the ball mill are yttria-stabilized zirconia ceramics, and the diameters include 25 mm, 15 mm, 10 mm and 5 mm, and the mass ratio of the grinding balls with diameters of 25 mm, 15 mm, 10 mm and 5 mm is 1:1:2:1; the ratio of the mass of the grinding balls to the total mass of the fine powder material is 10:1; the ball mill speed is 100 rpm and 200 rpm; the slag and the lithium slag are ball milled to a fine powder particle size passing through a 200 mesh sieve, and the glass and the alkali slag are ball milled to a fine powder particle size passing through a 200 mesh sieve;

[0027] (2) The fine powders of the slag, the glass, the lithium slag and the alkaline slag are weighed and mixed in a mass fraction ratio of 100:5.8:3.9:3.6, and a first mixed micro-powder is obtained after sand milling; the grinding balls of the sand mill are made of yttria-stabilized zirconia ceramic material, and the diameters include 3 mm, 1 mm and 0.5 mm, and the mass ratio of the grinding balls of 3 mm, 1 mm and 0.5 mm is 1:0.5:1; the ratio of the mass of the grinding balls to the total mass of the materials is 4:1; the main machine speed of the sand mill is 600 rpm, and the sand milling time is 2 h; the specific surface area of ​​the first mixed micro-powder is 380 m 2 / kg, D95 is not more than 30μm;

[0028] (3) Wetting and soaking the first mixed micropowder in deionized water at room temperature for 2 hours, filtering and freezing at -18°C for 5 hours, and then vacuum drying at 50°C for 4 hours, repeating the wetting and soaking, freezing and vacuum drying process twice, a total of three times, to obtain a second mixed micropowder;

[0029] (4) The second mixed micropowder is dispersed in a 2,2-dimethylpropanol solvent, and zinc nitrate with a final concentration of 0.01 mol / L and 2-methylimidazole with a final concentration of 0.02 mol / L are added. The mixed system is stirred and reacted at room temperature for 4 hours. After filtering, the mixture is washed with 2,2-dimethylpropanol solvent and dried to obtain the green high-performance slag micropowder.

[0030] Example 2

[0031] A slag micropowder, the preparation method of which comprises the following steps:

[0032] (1) Rolling and ball milling slag, lithium slag and alkali slag to obtain fine powder of each raw material; the rolling pressure is 100-120 MPa; the grinding balls of the ball mill use yttria-stabilized zirconia ceramics, and the diameters include 25 mm, 15 mm, 10 mm, and 5 mm, and the mass ratio of the grinding balls with diameters of 25 mm, 15 mm, 10 mm, and 5 mm is 1:1:2:1; the ratio of the mass of the grinding balls to the total mass of the fine powder material is 10:1; the ball mill speed is 100 rpm and 200 rpm; the slag and the lithium slag are ball milled to a fine powder particle size that passes through a 200 mesh sieve, and the alkali slag is ball milled to a fine powder particle size that passes through a 200 mesh sieve;

[0033] (2) The fine powders of the slag, the lithium slag and the alkaline slag are weighed and mixed in a mass fraction ratio of 100:3.9:3.6, and a first mixed micropowder is obtained after sand milling; the grinding balls of the sand mill are made of yttria-stabilized zirconia ceramic material, and the diameters include 3 mm, 1 mm and 0.5 mm, and the mass ratio of the grinding balls of 3 mm, 1 mm and 0.5 mm is 1:0.5:1; the ratio of the mass of the grinding balls to the total mass of the materials is 4:1; the main machine speed of the sand mill is 600 rpm, and the sand milling time is 2 h; the specific surface area of ​​the first mixed micropowder is 380 m 2 / kg, D95 is not more than 30μm;

[0034] Steps (3) and (4) are the same as those in Example 1.

[0035] Example 3

[0036] A slag micropowder, the preparation method of which comprises the following steps:

[0037] (1) Slag, glass and lithium slag are respectively subjected to roller pressing and ball milling to obtain fine powder of each raw material; the roller pressing pressure is 100-120 MPa; the grinding balls of the ball mill are yttria-stabilized zirconia ceramics, and the diameters include 25 mm, 15 mm, 10 mm and 5 mm, and the mass ratio of the grinding balls with diameters of 25 mm, 15 mm, 10 mm and 5 mm is 1:1:2:1; the ratio of the mass of the grinding balls to the total mass of the fine powder material is 10:1; the ball milling speed is 100 rpm and the rotation speed is 200 rpm; the slag and the lithium slag are ball milled to a fine powder particle size passing through a 200 mesh sieve, and the glass is ball milled to a fine powder particle size passing through a 200 mesh sieve;

[0038] (2) The fine powders of the slag, the glass, and the lithium slag are weighed and mixed in a mass fraction ratio of 100:5.8:3.9, and a first mixed micropowder is obtained after sand milling; the grinding balls of the sand mill are made of yttria-stabilized zirconia ceramic material, and the diameters include 3 mm, 1 mm, and 0.5 mm. The mass ratio of the grinding balls of 3 mm, 1 mm, and 0.5 mm is 1:0.5:1; the ratio of the mass of the grinding balls to the total mass of the materials is 4:1; the main machine speed of the sand mill is 600 rpm, and the sand milling time is 2 h; the specific surface area of ​​the first mixed micropowder is 380 m 2 / kg, D95 is not more than 30μm;

[0039] Steps (3) and (4) are the same as those in Example 1.

[0040] Example 4

[0041] A slag micropowder, the preparation method of which comprises the following steps:

[0042] Steps (1) and (2) are the same as in Example 1;

[0043] (3) The first mixed fine powder is dispersed in a 2,2-dimethylpropanol solvent, and zinc nitrate with a final concentration of 0.01 mol / L and 2-methylimidazole with a final concentration of 0.02 mol / L are added. The mixed system is stirred at room temperature for 4 hours, filtered, washed with 2,2-dimethylpropanol solvent, and dried to obtain the slag fine powder.

[0044] Example 5

[0045] A slag micropowder, the preparation method of which comprises the following steps:

[0046] Steps (1) and (2) are the same as in Example 1;

[0047] (3) Wetting and soaking the first mixed powder in deionized water at room temperature for 2 hours, filtering and freezing at -18°C for 5 hours, and then vacuum drying at 50°C for 4 hours. Repeat the wetting, soaking, freezing and vacuum drying process twice, a total of three times, to obtain the slag powder.

[0048] Example 6

[0049] A slag micropowder, the preparation method of which comprises the following steps:

[0050] (1) Slag, glass, lithium slag and alkali slag are respectively subjected to roller pressing and ball milling to obtain fine powder of each raw material; the roller pressing pressure is 100-120 MPa; the grinding balls of the ball mill are yttria-stabilized zirconia ceramics, and the diameters include 25 mm, 15 mm, 10 mm and 5 mm, and the mass ratio of the grinding balls with diameters of 25 mm, 15 mm, 10 mm and 5 mm is 1:1:2:1; the ratio of the mass of the grinding balls to the total mass of the fine powder material is 10:1; the ball mill speed is 100 rpm and 200 rpm; the slag and the lithium slag are ball milled to a fine powder particle size passing through a 200 mesh sieve, and the glass and the alkali slag are ball milled to a fine powder particle size passing through a 200 mesh sieve;

[0051] (2) The fine powders of the slag, the glass, the lithium slag and the alkaline slag are weighed and mixed in a mass fraction ratio of 100:5.8:3.9:3.6, and the slag powder is obtained by sand grinding; the grinding balls of the sand mill are made of yttria-stabilized zirconia ceramic material, and the diameters include 3 mm, 1 mm and 0.5 mm, and the mass ratio of the grinding balls of 3 mm, 1 mm and 0.5 mm is 1:0.5:1; the ratio of the mass of the grinding balls to the total mass of the materials is 4:1; the main machine speed of the sand mill is 600 rpm, and the sand grinding time is 2 h; the specific surface area of ​​the first mixed powder is 380 m 2 / kg, D95 is not greater than 30μm.

[0052] The slag powder described in Examples 1-6 was applied to commercially available 425 grade silicate cement to detect the activity index of the slag powder. The test results are shown in the following table:

[0053]

[0054]

[0055] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing green high-performance slag micropowder, characterized in that: The following steps are involved: (1) Rolling and ball milling slag, glass, lithium slag and alkali slag to obtain fine powder of each raw material; (2) weighing fine powders of various raw materials in proportion, mixing them, and preparing a first mixed fine powder after sand grinding; wherein the mass fraction ratio of the fine powders of the slag, the glass, the lithium slag, and the alkaline slag is 100: (4-8): (2-6): (1-5); (3) Wetting and soaking the first mixed micropowder for 1-24 hours, freezing after solid-liquid separation, and then vacuum drying, repeating the wetting and soaking, freezing and vacuum drying process to obtain a second mixed micropowder; wherein the freezing temperature is minus 4°C to minus 20°C; the vacuum drying temperature is 25-60°C, and the drying time is 1-8 hours; the total number of repetitions of the wetting and soaking, freezing and vacuum drying process is 2-4 times; (4) dispersing the second mixed micropowder in an alcohol solvent, adding zinc nitrate and 2-methylimidazole, stirring the mixed system at room temperature for reaction for 0.5-6 hours, and washing and drying in sequence after solid-liquid separation to obtain the green high-performance slag micropowder.

2. The method for preparing green high-performance slag micropowder according to claim 1, characterized in that: In step (1), the particle size of the fine powder of the slag and the lithium slag is 200-300 mesh; the particle size of the fine powder of the glass and the alkali slag is 200-400 mesh.

3. The method for preparing green high-performance slag micropowder according to claim 1, characterized in that: The grinding balls of the sand mill in step (2) are made of yttria-stabilized zirconia ceramic material, and the mass ratio of the grinding balls with diameters of 3 mm, 1 mm, and 0.5 mm is (0-2):(0.5-3):1; the ratio of the mass of the grinding balls to the total mass of the material is (3-8):1; the main machine speed of the sand mill is 500-1600 rpm, and the sand milling time is 1-10 h.

4. The method for preparing green high-performance slag powder according to claim 1, characterized in that: The specific surface area of ​​the first mixed micropowder is 350-400m 2 / kg, D95 is not greater than 40μm.

5. The method for preparing green high-performance slag powder according to claim 1, characterized in that: In step (4), the alcohol solvent is one or more of methanol, ethanol, isopropanol, n-butanol, 2,2-dimethylpropanol, n-hexanol, n-heptanol, and n-octanol.

6. The method for preparing green high-performance slag powder according to claim 1, characterized in that: The concentration of zinc nitrate in the mixed system is 0.005-0.01 mol / L, and the concentration of 2-methylimidazole in the mixed system is 0.01-0.02 mol / L.

7. A green high-performance slag powder, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Ultrahigh-strength cement-based repairing material modified by metal organic framework material

    CN108383446A

  • Green high-performance superfine slag powder

    CN113772984A